(3GdHVGYI GdeRLGIs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg HLejY eMGeOg (B... (3GdeLdS GdChd aj HOA GdfcGM hCUd Ndbg, bGd Gddg YR ef bGFd aj eMce cJGHg GdYRjR(B: (3jG GjgG GdfGS GJbhG QHce GdPj Ndbe ef faS hGMOI hNdb efgG RhLgG hHK efgeG QLGdG cKjQG hfSGA, GdeQGO HGdfaS GdhGMOI gh BOes
(3BNQgG (B:s
(3BNQgG(B: (3aGfHYK efg GdOe cGdejRGH aLaa ef hLgg hdMjJg hbGd(B: (3gcPG Cdbi Gddg hGfG eNVH HOej eZUhH Ydnqj Mbj, hSjYde GdPjf XdehG Gj efbdH jfbdHhf(B. (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B3: 71s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs